LORD JAGANNATHA OF PURI IN EASTERN INDIA: A UNIQUE DEITY OF THE HINDU SOCIETY OF THE WORLD - Mohapatra, Ratnakar (International Journal of Psychosocial Rehabilitation, 2020)
Lord Jagannath ofPuri is famous in India as a Lord of Universe and its temple is considered by millions of Hindus as animportant Vaishnava shrine of world. The celebrated temple of Lord Jagannatha is also well-known throughout the world for its religious sanctity. In fact, Lord Jagannatha occupies a vital position in the religious history of Odisha. The cult of Jagannatha has a distinct message for the whole of Indian people. Lord Jagannathawas initially named as Nilamadhava, Paramesvara, Purusottama and in later as the present name. The place of Lord Purusottama (Jagannatha) of Puri is one of the important cultural centers of Odisha and it is also famous throughout India as a place of pilgrimage. The spot of Ratnasimhasana of Lord Jagannatha of Puri has been considering by pilgrims as the holiest place of Eastern India from time immemorial. The daily rituals of Lord Jagannatha are as old as the temple itself. Navakalevara ceremony of Lord Jagannatha of Puri is the symbolic of traditional Vedic worship mixed with the tribal worship of Daitas. The annual Car festival of Lord Jagannatha of Puri is enthusiastically celebrated, for which, a large numbers of pilgrims arrive to this place and such type of huge crowded chaotic festival has justified the word ‘Jagannatha’.The celebrated temple of Lord Jagannatha possesses a pivotal position in the religious history of Odisha.The aim of this paper is to study briefly all the aspects ofLord Jagannatha of Purias far as practicable on the part of present author. Methodologically, both the primary and secondary sources have been used here to access Lord Jagannatha of Puri as a unique deity of the Hindu society of the world.